Researching translation competence by PACTE group / Amparo Hurtado Albir - Hurtado Albir, Amparo
This volume is a compendium of PACTE Group's experimental research in Translation Competence since 1997. The book is organised in four main parts and also includes eight appendices and a glossary. Part I presents the conceptual and methodological framework of PACTE's Translation Competence research design. Part II focuses on the methodological aspects of the research design and its development: exploratory tests and pilot studies carried out; experiment design; characteristics of the sample population; procedures of data collection and analysis. Part III presents the results obtained in the experiment related to: the Acceptability of the translations produced in the experiment and the six dependent variables of study (Knowledge of Translation; Translation Project; Identification and Solution of Translation Problems; Decision-making; Efficacy of the Translation Process; Use of Instrumental Resources); this part also includes a corpus analysis of the translations. Part IV analyses the translators who were ranked highest in the experiment and goes on to present final conclusions as well as PACTE's perspectives in the field of Translation Competence research.